Accountability of Village Head's in The Use Allocation of Village Fund - Nahdliyah, Hadziqotun; khitam, Muhammad chusnul; Priyadi, Ferdhi Riski (Jurnal Independent, 2024)
ABSTRACT The management of village funds needs to be assisted so that they are used according to the rules. The problem formulation is: What is the Accountability of the Village Head in Using the Village Fund Allocation? Management of Village Fund Allocations is regulated in Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages. The realization of the Implementation of Village Fund Allocations is reported in each fiscal year no later than 3 (three) months after the fiscal year ends along with the APBDesa Accountability to the Regent through the Subdistrict Head. Apart from the administration and implementation aspect, there is criminal legal liability in the management of Village Fund Allocations related to misuse of Village Fund Allocations by the Village Head, which can occur because of not following the Budget Plan or because of the Village Head's behavior and lifestyle which causes state losses.